Implementasi Aplikasi Program Keamanan Buku Tamu Dalam Meningkatkan Perlindungan Data Pengunjung - Oviance Vinsensius Bulu; Stefanus D.I.Mau; Diana Reby Sabawaly (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Manual guest book management is still widely used in government agencies, but this method has several weaknesses, such as low efficiency, potential recording errors, and the risk of visitor personal data leakage. Along with advances in information technology, implementing a digital guest book application with security features is a solution to improve efficiency, accuracy, and visitor data protection. This study aims to implement a web-based guest book security program application to enhance visitor data protection at the Southwest Sumba Regency Leadership Communication and Protocol Office, and to evaluate the system's effectiveness in supporting transparency and ease of reporting. The research method used is Research and Development (R&D), with stages of system design, development, and testing. The application was developed using the PHP programming language as server-side scripting and supported by an integrated database. Data collection techniques included observation, interviews, and documentation. The results show that implementing a web-based guest book security program application can increase the efficiency of the recording process, improve data accuracy, and strengthen visitor data protection through authentication and access control mechanisms. The developed system also simplifies the reporting and monitoring of visitor data, making it more effective than the previously used manual system.